2012
DOI: 10.1016/j.nbd.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance induces neuroinflammation and impairment of learning and memory

Abstract: Hospitalized patients can develop cognitive function decline, the mechanisms of which remain largely to be determined. Sleep disturbance often occurs in hospitalized patients, and neuroinflammation can induce learning and memory impairment. We therefore set out to determine whether sleep disturbance can induce neuroinflammation and impairment of learning and memory in rodents. Five to 6-month-old wild-type C57BL/6J male mice were used in the studies. The mice were placed in rocking cages for 24 hours, and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 58 publications
(77 reference statements)
4
95
1
Order By: Relevance
“…Our results did not replicate the learning and memory defects demonstrated by Derecki et al in IL-4 KO animals (Derecki et al 2010) but as noted above anxiety (Harrison et al 2009) and sleep disturbance (Zhu et al 2012) can significantly alter mouse cognitive performance. In addition, different investigative teams can observe phenotype disparities when behavior is examined.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our results did not replicate the learning and memory defects demonstrated by Derecki et al in IL-4 KO animals (Derecki et al 2010) but as noted above anxiety (Harrison et al 2009) and sleep disturbance (Zhu et al 2012) can significantly alter mouse cognitive performance. In addition, different investigative teams can observe phenotype disparities when behavior is examined.…”
Section: Discussioncontrasting
confidence: 98%
“…Derecki et al indicated that training and testing of mice was performed during their inactive cycle (sleep period) (Derecki et al 2010). Recently, Zhu et al found that a single episode of sleep disturbance induces impaired learning and memory in mice (Zhu et al 2012). Since we trained and tested mice during their active cycle (facilitated by our use of reverse light cycle housing), we sought to avoid sleep disturbance confounds identified by Zhu et al To support these memory results, we also used object location recognition testing (spatial memory) and novel object recognition testing (non-spatial memory) (York et al 2012, Weible et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the hippocampal volume50 51 and orbitofrontal and parietal grey matter52 has been observed, or brain volume changes have not been found 53 54. Poor sleep and sleep loss are proposed to induce neuroinflammation55 and disruptions in the production and development of new neurons 56. Furthermore, accumulation of amyloid-β may disrupt the sleep-wake cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, loss of sleep can activate anti-oxidant pathways in the brain, including the Unfolded Protein Response, suggesting that it does result in oxidative stress [181]. Loss of sleep can induce neuroinflammation [182], while both too much sleep, and too little, is associated with the metabolic syndrome [183].…”
Section: Is Thinking Anti-inflammatory?mentioning
confidence: 99%